TOXICITY TESTING APPLIED TO WASTEWATER TREATMENT - Değermenci, Gökçe Didar (Engin TUTKUN, 2017)
Populationgrowth and increasing water consumption result in problems related to waterthroughout the world. Therefore, the number of the studies on the re-use ofpurified water and meeting the discharge limits has recently increased. Whilethe purified industrial and domestic wastewaters are being discharged into thereceiving environment, they should not contain micro-pollutants such as drugs,pesticides and especially chemicals leading to endocrine disorders anddischarge limits should be met. These micro-pollutants lead to disruptions inthe ecology of the aquatic and terrestrial environment. In recent years,toxicity tests have been implemented and bio-monitoring has been performed inorder to determine the pollution parameters. The main aims of the toxicitytests are to determine harmless concentrations on the living creatures and todetect the quality of the surface waters or the level of toxicity of thepollution discharged. The studies aiming at determining the toxic effects ofwaste waters are conducted in consideration of their short-term and long-termeffects on the freshwater (Selenastrum capricornutum) and saltwater (Artemiasalina) algae, invertebrates (Dapnia magna) and fish (Mysidopsis bahia) so asto obtain results swiftly and to achieve favourable operating costs. Acutetoxicity is the toxic substance dose (LD50) or concentration (LC50) needed forkilling at least 50% of the experiment organisms or the median effectiveconcentration (EC50) sufficient for immobilizing them. Such test kits asMicrotox, Biotox, Lumistox and Toxalert and respirometric measurements are alsocommonly used. European Union countries discharge their domestic and industrialwastewaters into the receiving environment in line with the toxicity limitvalues in order to protect their existing resources. In our country, toxicity measurementlimit values should be added to the discharge limits.
Keywords: TOXICITY TESTING APPLIED TO WASTEWATER TREATMENT; 13. Climate action; 6. Clean water